Gender and Perspective in Scarlet Street - Carlucci, Fernando Valenzuela (Revista PHILIA | Filosofia, Literatura & Arte, 2019)
This paper presents an interpretation of the 1945 forbidden film Scarlet Street in a way so as to touch the problem of gender in film noir. Firstly, I give an ac-count of film noir, agreeing with Robert Pippin’s argument concerning film genres. Then, I claim that time and repetition, irony and hierarchy, art and per-spective constitute the core subjects explored in Scarlet Street. Furthermore, I try to connect all the subjects into a single one. My point is to show how art, perspective, time, repetition, irony and hierarchy are articulated in the main character’s gender identity. Finally, I suggest there is a deep connection be-tween the movie’s character constitution and Cavell’s understanding of gender and agency. Keywords: Film. Gender. Psychoanalysis. Cavell. Freud.